Multiple flare-angle horn feeds for sub-mm astronomy and cosmic microwave background experiments - Leech, J; Tan, B; Yassin, G; Kittara, P; Wangsuya, S; Treuttel, J; Henry, M; Oldfield, M; Huggard, P (2011)
Context. The use of large-format focal plane imaging arrays employing multiple feed horns is becoming increasingly important for the next generation of single dish sub-mm telescopes and cosmology experiments. Such receivers are being commissioned on both general purpose, common user telescopes and telescopes specifically designed for mapping intensity and polarisation anisotropies in the cosmic microwave background (CMB). Telescopes are currently being constructed to map the CMB polarisation that employ hundreds of feeds and the cost of manufacturing these feeds has become a significant fraction of the total cost of the telescope. Aims. We have developed and manufactured low-cost easy-to-machine smooth-walled horns that have a performance comparable to the more traditional corrugated feed horns that are often used in focal plane arrays. Our horns are much easier to fabricate than corrugated horns enabling the rapid construction of arrays with a large number of horns at a very low cost. Methods. Our smooth walled horns use multiple changes in flare angle to excite higher order waveguide modes. They are designed using a genetic algorithm to optimise the positions and magnitudes of these flare angle discontinuities. We have developed a fully parallelised software suite for the optimisation of these horns. We have manufactured prototype horns by traditional electroforming and also by a new direct drilling technique and we have measured their beam patterns using a far-field antenna test range at 230 GHz. Results. We present simulated and measured far-field beam patterns for one of our horn designs. They exhibit low sidelobe levels, good beam circularity and low cross-polarisation levels over a fractional bandwidth of 20%. These results offer experimental confirmation of our design technique, allowing us to proceed confidently in the optimisation of horns with a wider operational bandwidth. The results also show that the new manufacturing technique using drilling is successful, enabling the fabrication of large format arrays by repeatedly drilling into a single aluminium plate. This will enable the construction of focal plane arrays at a very low cost per horn. Conclusions. We have developed a new type of high performance feed horn that is fast and easy to fabricate. Having demonstrated the efficacy of our horn designs experimentally, we are building and testing a prototype focal plane array of 37 hexagonally close packed horns. This prototype array will be an important step towards building a complete CMB mapping receiver using these feed horns. © 2011 ESO.